Utilization of ECMO with fiberoptic bronchoscopy for pediatric patients with lethal pulmonary hemorrhage unresponsive to conventional mechanical ventilation - Lu, Siwei; Sun, Yuelin; Chen, Yingfu; Fu, Yueqiang; Li, Jing; Liu, Chengjun (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the safety and efficacy of extracorporeal membrane oxygenation (ECMO) combined with fiberoptic bronchoscopy in children with life-threatening pulmonary hemorrhage that does not respond to conventional mechanical ventilation.MethodsFrom October 2019 to June 2022, four pediatric patients with life-threatening pulmonary hemorrhage requiring ECMO support were admitted to our hospital. Based on their weight and vascular conditions, either venoarterial (VA)-ECMO or venovenous (VV)-ECMO was selected. The anticoagulation strategy was tailored, and fiberoptic bronchoscopy was performed to assess airway bleeding and remove blood clots.ResultsThe study involved four patients. Case 1 sustained injuries from a traffic accident, Case 2 experienced combined injuries from a high fall, Case 3 had pulmonary vascular malformation, and Case 4 presented with anti-neutrophil cytoplasmic antibody-associated vasculitis. Case 1 underwent VA-ECMO with carotid artery and vein cannulation, whereas the other patients received VV-ECMO with jugular–femoral vein cannulation. During cannulation, heparin was administered at 0.5 mg/kg. Protamine was subsequently used to neutralize heparin based on the bleeding situation. Anticoagulation was initiated 24 h after ECMO commencement in Cases 1, 2, and 4, maintaining an activated clotting time (ACT) of 160–180 s. In Case 3, active bleeding was observed in the tracheal tube post-ECMO initiation. Protamine was administered to reverse the effects of heparin, and anticoagulation was withheld for the first 72 h. After a second interventional embolization of the vascular malformations, the active bleeding ceased. Two fiberoptic bronchoscopies revealed no further bleeding, and anticoagulation was initiated at 5 U/kg/h to maintain an ACT of 160 s. Coagulation parameters, including ACT, blood analysis, and thromboelastography, were closely monitored, and heparin dosages were adjusted accordingly. Heparin was paused 1 h before each fiberoptic bronchoscopy and resumed afterward. During ECMO, all patients successfully underwent fiberoptic bronchoscopy. Cases 2 and 3 required three and six procedures, respectively. Substantial thrombi were removed from the airways of Cases 2 and 3. All patients survived, and they were discharged without complications related to ECMO or fiberoptic bronchoscopy.ConclusionFor children with life-threatening pulmonary hemorrhage that did not respond to conventional mechanical ventilation, the combination of ECMO and fiberoptic bronchoscopy represents a promising therapeutic option. ECMO rapidly corrects hypoxemia and provides respiratory support, whereas fiberoptic bronchoscopy effectively clears blood clots and facilitates lung re-expansion. Under an individualized anticoagulation strategy, this combined approach is both safe and effective, significantly improving clinical outcomes in pediatric patients with life-threatening pulmonary hemorrhage.